Evaluation of Gold Nanoparticles in Terms of Their Use in Biomedical Applications - Burcu Biterge-Süt; Elif Canpolat (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Recently nanotechnology has become an integral part of modern biomedical applications. Accordingly, nanoparticles are considered as promising components for the development of innovative tags, probes, biosensors and carrier molecules for drug delivery. Spherical colloidal gold nanoparticles (AuNPs) are prime candidates to be utilized for these purposes due to their useful physical properties. However, in order for the gold nanoparticles to be used in nanomedicine, their biological properties should be extensively studied as well. Therefore, in this paper we chemically synthesized gold nanoparticles and studied their physical and biological characteristics to determine their potential use in medicine. Gold nanoparticles were synthesized by the reduction of chloroauric acid (HAuCl4) solution with sodium citrate. The physical properties of the AuNPs were determined by UV–vis spectrophotometer and Zetasizer readings. The antimicrobial activity of the newly synthesized gold nanoparticles on Escherichia coli, Salmonella infantis, Salmonella kentucky, Salmonella typhimurium, Salmonella enteritidis, Pseudomonas aeruginosa, Listeria monocytogenes, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Bacillus subtilis and Candida albicans were investigated via disk diffusion method. We found that the AuNPs were monodisperse, stable and not prone to aggregation with an average size of 22.12 nm and an emission band at 522 nm. The disk diffusion tests revealed that the gold nanoparticles did not have a significant growth inhibitory effect on the pathogens tested. In conclusion, here we showed the successful synthesis of gold nanoparticles by a safe and non-toxic method. Furthermore, our evaluation of the antimicrobial activity of these nanoparticles suggests that these molecules could be considered as biologically safe molecules for future medical applications.